Anhedonia in young people with first episode psychosis: a longitudinal study. (31st July 2020) - Pelizza, Lorenzo; Garlassi, Sara; Azzali, Silvia; Paterlini, Federica; Scazza, Ilaria; Chiri, Luigi Rocco; Poletti, Michele; Pupo, Simona; Raballo, Andrea
Abstract: Aim: Previous research observed deficits in pleasure experience in chronic schizophrenia, but little is known about anhedonia in early psychosis. Aim of this study is: (1) to examine anhedonia in distinct help-seeking subgroups of young people identified through the First Episode Psychosis (FEP) criteria, (2) to investigate its correlations with psychopathology in the FEP sample, and (3) to monitor longitudinally its stability in the FEP group along 1-year follow-up period. Materials and methods: All participants (137 FEP and 95 nonpsychotic psychiatric controls [i.e. non-FEP]), aged 13–35 years, completed the Comprehensive Assessment of At-Risk Mental States (CAARMS), the Schizotypal Personality Questionnaire – Brief version (SPQ-B), the Brief O-LIFE questionnaire (BOL), and the World Health Organization Quality of Life – Brief version (WHOQOL-BREF). We used two different indexes of anhedonia: CAARMS 'Anhedonia' item 4.3 and BOL 'Introvertive Anhedonia' subscale scores. Results: In comparison with non-FEP, FEP patients showed higher baseline anhedonia scores. After 1-year follow-up period, FEP individuals had a significant decrease in severity of anhedonia scores. In the FEP group, anhedonia showed significant, enduring (over time) correlations with impaired role functioning, negative symptoms, comorbid depression, poorer self-perceived quality of life and specific schizotypal personality traits (i.e. interpersonal deficits). Conclusions: Anhedonia is relevant in the early phase of psychosis and its severity is associated with functioning deterioration and a bad quality of life.